Mediator effect of caregiver burden on the association between disability and quality of life among older adults - Aarón Salinas-Rodríguez; Betty Soledad Manrique-Espinoza; Julio César Montañez-Hernández (Instituto Nacional de Salud Pública, 2022)
Objective. To estimate the association of disability and quality of life considering the potential mediating role of caregiver burden among a sample of older Mexican adults and their caregivers. Materials and methods. Cross-sectional study with 93 dyads (elderly/caregivers) conducted in 2018 in five localities (urban and rural) of the State of Mexico. The quality of life (QoL) was determined using the WHOQoL (WHO Quality of Life) instrument. Disability was measured by assessing the basic activities of daily living (BADL), and the caregiver burden was evaluated by the Zarit Burden Interview (ZBI). Results. The results showed that BADL disability is associated with a lower QoL (total effect: -14.3; 95%CI: -20.2,-8.4) and that a significant proportion of this association can be attributable to caregiver burden (25.0%; 95%CI: 17.9,43.2). Conclusions. Our findings show the need for designing effective interventions that prevent or ameliorate the adverse effects of caregiver burden.